Evaluation of different natural foods on maturation of freshwater crayfish (Cherax quadricarinatus) - Fatwana, Nurullah; Komariyah, Siti; Rosmaiti, Rosmaiti; Hasri, Iwan (Universitas Malikussaleh, 2021)
This study was aimed to examine the different natural feeds on the maturnity of freshwater crayfish. The study was conducted on November 20th - January 21th 2021 in the UPTD BBI Lukup Badak, Takengon, Aceh Tengah. Test fish used is seed of cherax quadricarinatus measuring 52-75 g. Methods used in this study was Completely Randomized Design (CRD) with 4 treatments and 3 replications. The treatments in this study were P1 (Tubifex), P2 (505 tubifex, 255 carrots, and 25% sweet potatoes), P3 (50% tubifex, 25% bean sprouts, and 25% sweet potatoes), and P4 (50% tubifex, 25% papaya, and 25% sweet potatoes). Seeds of fish was put in a container maintenance with 42 liters of water volume and density of 1 tails per container. Frequency of feeding was 3 times a day at 08.00 am, 16.00 pm and 20.00 pm. The results showed that different natural feeding teratments had a very significant effect on the absolute weight and gonad maturity indexs (IKG).Keywords: Absolute weight; Cherax quadricarinatus; Gonad; Natural feed.